Pathology of Fowl Paratyphoid and Molecular Detection of Its Pathogen in Layer Chickens (Annals of Bangladesh Agriculture, 2021)
The study was aimed to ascertain the pathology of fowl paratyphoid and molecular detection of its causal agent (Salmonella spp) in chickens. Pathological and swab samples were collected from layers in Gazipur district, Bangladesh. For observing the gross and microscopic lesions of different organs necropsy and histopathology were done, and to isolate and identify the Salmonella spp, different bacteriological tests and Polymerase Chain Reaction (PCR) were performed. Swabs from 150 chickens showed 66% of salmonellosis. Gram’s staining of isolated bacteria showed pink colored rod shaped bacilli. In biochemical tests, Salmonella fermented dextrose, maltose, xylose, arabinose, dulcitol, mannitol except lactose and sucrose. Investigation of gross lesions at necropsy revealed hemorrhage and congestion in intestine, liver, spleen and ovaries. Necrotic foci were found in liver and spleen, and button like ulceration in cecal tonsils as well. Microscopic lesions included hemorrhage and focal necrosis in liver and spleen. Congestion and infiltrations of inflammatory cells were observed in small intestine. Ovary was hemorrhagic and there was infiltration of heterophils. Biochemically positive and isolated Salmonella organisms were confirmed by PCR method using invA and IE1 primers. The final results showed that a total of 91.7% Salmonella suspected cultures were confirmed as Salmonella Enteritidis.Ann. Bangladesh Agric. (2020) 24(2) : 47-57